Enhancement of high strength concrete performance by utilising nano waste paper sludge ash / Aidan Newman … [et al.] - Newman, Aidan; Muhd Sidek, Muhd Norhasri; Mohd Saman, Hamidah; Alisibramulisi, Anizahyati (Universiti Teknologi MARA, 2021)
High strength concrete (HSC) is an amazing breakthrough in the history of construction material. Due to its high strength, durability, and economic value, it has been used in large-scale construction with a unique structure design not achievable by conventional concrete. However, HSC uses a high amount of cement powder which contributes to its overall strength. However, it will require high cement consumption and increases carbon dioxide emission. Waste paper sludge ash (WPSA) is utilized in cement and has improved concrete properties. Nano engineered WPSA might further enhance HSC capabilities. This research focused on the physical and fresh properties of HSC with partial replacement of nano-engineered WPSA to cement through experimental investigation. The HSC produced in this research has a targeted strength of more than 40MPa with a fixed water-cement ratio of 0.2. The WPSA was oven-dried and was sieved to a particle size of 212 micrometers. Then, it was milled until a nano-size particle is obtained. The nano WPSA is used to replace cement in the HSC mix with a replacement percentage of 1%, 3%, 5%, 7%, and 10%. The new properties of the concrete were measured by conducting the flow table test, and the physical property was determined by conducting the compressive test. Compressive tests were conducted for 1, 3, 7, 14, and 28 days with a cube sample size of 50mm x 50mm x 50mm. This research shows that 1% of nano WPSA replacement tends to improve the compressive strength of the HSC concrete by 10.7% compared to the control sample. On the other hand, the 1% replacement of nano WPSA in HSC did not affect the concrete's workability compared to the control sample. The conventional HSC properties were improved with less usage of cement with the use of WPSA.